Efektivitas Program Puspaga dalam Meningkatkan Kehidupan dan Ketahan Keluarga di Tingkat Balai RW - Marcel Mochammad Reza Ardito; Anggraeny Puspaningtyas (Jurnal Media Administrasi, 2023)
Family problems are a problem that occurs quite often in everyday life, where these problems include several forms of life dynamics, behavior and life patterns/attitudes that can disrupt the household and family. Therefore, efforts are needed to unite the responsibilities of parents and the obligations of the state and local governments to help overcome family problems, one way is by establishing a Family Learning Center (PUSPAGA) which aims to be a service to improve family life and resilience. In achieving the research objectives, the research used descriptive qualitative methods with analytical methods. Data collection techniques are carried out by conducting interviews, observation and documentation. The results of this research show that the PUSPAGA program in improving the lives and resilience of families at the RW hall level, especially RW Hall 02 Kel. Kali Kedinding Land, District. Kenjeran is running quite well due to several supporting factors such as performance, initiative, and interactiveness from the writers and PUSPAGA RW service employees in carrying out promotions / socialization and consultation / counseling.